Clinical referral to the NHS following multi-cancer early detection test results from the NHS-Galleri trial - Lowenhoff, Ian; Dolly, Saoirse; Dowinton Smith, Rebecca; Hiom, Sara; Holmes, Liz; Johnson, Peter; King, Laura; Neal, Richard D.; Round, Thomas; Swanton, Charles; Lee, Lennard Y. W. (Frontiers in Oncology, 2025)
IntroductionThe large, randomised, controlled NHS-Galleri trial (NCT05611632) is assessing the clinical utility of a multi-cancer early detection (MCED) test for asymptomatic cancer screening in England. We describe how we enabled the efficient referral of trial participants into existing National Health Service (NHS) urgent suspected cancer pathways for diagnostic investigations. Methods/ResultsParticipants were enrolled across eight of the 21 Cancer Alliance regions in England, served by 56 Hospital Trusts. We used the existing NHS e-Referral Service (e-RS) and a new e-referral form to enable referrals from the trial into any participating Trust, and to standardise information provided with trial participant referrals. Referrals were made by trial nurses directly into secondary care, minimising any additional burden on primary care. At most Trusts, a designated Trust-based referral coordinator triaged referrals and referred participants into the most appropriate local pathway, selected based on the tissue type or organ associated with the cancer signal (cancer signal origin; CSO). At other Trusts, trial nurses referred participants into the appropriate pathway. Guidance mapping predicted CSO(s) to NHS pathways was provided by the trial team to help clinicians understand trial referrals. The trial team and Trust referral coordinators were responsible for central and Trust-level safety netting measures, respectively. ConclusionsTo our knowledge, the NHS-Galleri trial has established the first model for the standardised clinical referral of asymptomatic individuals from a trial into NHS standard-of-care cancer pathways. We hope insights from our work could help accelerate screening trial conduct in the UK, and support MCED population screening programme implementation in future.